Process optimization and identification of defective products with ProModel software in the production of “J&N E.I.R.L” compactbono - Quispe Vásquez, Luis Roberto; Gonzales Abanto, Wilson Alcides; Salazar Terrones, Yudith; Sánchez Abanto, Elvita del Socorro; Castillo Marín, Magda Mariela; Quiroz Delgado, Irelita Deyli; Vera Gallardo, Jhoseline Lisbeth (LACCEI, 2024)
The purpose of this research was the optimization of processes and identification of those defective products that affect production, as well as delay the processes, which is why it seeks to improve the development of each compactbono process in the company “J&N E.I.R.L.”, a company dedicated to the commercialization of agricultural and chemical fertilizers. To do this, solutions were applied with the ProModel software where we seek to reach an optimal solution and make correct decisions in terms of helping to improve each aspect of production and increase the profits of the same company. The ProModel digital tool was used in order to simulate the transportation system using conveyor belts where each transformation process of the resource to be worked on was analyzed, as well as the reduction of time in terms of compacting and defective parts thereof to decide which resource is suitable for delivery, thus seeking to progressively increase profits. The ProModel software was duly applied, which is characterized by providing the details of each process, considering exact times for each required transformation, where the locations that determined the stages of problems were determined and convenient solutions were found, optimizing the company's processes.